Nucleotide sequence of the 5'- and 3'- domains for rabbit 18S ribosomal RNA. - Lockard, R E (1982)
By direct RNA sequence analysis we have determined the primary structures of both the 5' and 3' domains for rabbit 18S ribosomal RNA. Purified 18S rRNA was labeled in vitro at either its 5' or 3' terminus with 32P, base-specifically fragmented enzymatically and chemically, and the resulting fragments electrophoretically fractionated by size in adjacent lanes of 140 cm long polyacrylamide sequencing gels run in 90% formamide. A phylogenetic comparison of both the mammalian 5' proximal 400 residues and the 3' distal 301 nucleotides with the previously determined yeast and Xenopus laevis 18S rRNA sequence shows extensive conservation interspersed with tracts having little homology. Clusters of G + C rich sequences are present within the mammalian 5' domain which are entirely absent in both the Xenopus laevis and yeast 18S rRNAs. Most base differences and insertions within the mammalian 18S rRNA when compared with yeast or Xenopus rRNA result in an increase in the G + C content of these regions. We have found nucleotide sequence analysis of the ribosomal RNA directly permits detection of both cistron heterogeneities and mapping of many of the modified bases.